Developing antitobacco mass media campaign messages in a low-resource setting: experience from the Kingdom of Tonga. Issue 3 (11th March 2016) - Sugden, C; Phongsavan, P; Gloede, S; Filiai, S; Tongamana, V O
Abstract : Tobacco use has become the leading cause of preventable death in Tonga, a small island nation in the South Pacific. One pragmatic and economical strategy to address this worrying trend is to adapt effective antitobacco mass media materials developed in high-income countries for local audiences. Using Tonga as an example, this paper shares the practical steps involved in adapting antitobacco campaign materials for local audiences with minimal resources, a limited budget and without the need for an external production team. The Tongan experience underscores the importance of an adaptation process that draws from evidence-based best-practice models and engages local and regional stakeholders to ensure that campaign materials are tailored to the local context and are embedded within a mix of antitobacco strategies.